Maternal Risk Factors in Women With Breast Cancer in AlNajaf Province (Indian Journal of Forensic Medicine & Toxicology, 2021)
Recently, breast cancer has been considered as an increasing problem specially in Iraq . This study wasdesigned to investigate maternal risk factors of breast cancer in Al-Najaf Province . A Convenience sampleof (40) patients was taken in this study during the period from Dec. .2019 to Apr. 2020 . The result of thepresent study shows that the majority of the women were between the age (30-40) years show the breastcancer increase in this age group. The results of the current study also showed that the vast majority at thewomen were married. The current study also showed that about (27.5%) and (22%) at the studied women aresuffering from hypertension and diabetes mellitus respectively. The present study reveal that about (32.5)ofthe women did not practice breast feeding ,(42.5) of them less than 2 years breast feeding. The present studyrevealed that about 60%of the women didn’t exposed to passive smoking and 40% of the women exposedto passive smoking , other study explain the second hand smoke have been suggested to increase the riskof breast cancer. The present study indicated that approximately all investigated women (39of 40)have nomedical history of ovarian polycystic disease . It was concluded that the most contributing risk factors in theoccurrence Education, BMI , contraceptive use ,passive smoking and age. It is recommended to establishan education program to enhance the awareness of women about the risk factors that have been recorded inthis study .
Keywords: Breast Cancer, Maternal Risk Factor , Women